2019
DOI: 10.1371/journal.pone.0222205
|View full text |Cite
|
Sign up to set email alerts
|

Living on the edge - circadian habitat usage in pre-weaning European hares (Lepus europaeus) in an intensively used agricultural area

Abstract: Over the last decades, the European hare (Lepus europaeus) has become the subject of many interdisciplinary studies due to the sharp Europe-wide population decline. In European hares, the first stage of life until weaning and the subsequent dispersal have been sparsely studied, in particular, habitat selection, movements and survival rate, as juveniles´ precocial lifestyle is dominated by concealment, motionlessness and inconspicuousness. In this study, free-living juvenile European hares (leverets) were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…This can be explained by the fact that leverets of the genus Lepus leave their birth area between the second and fourth day of life to find their own daily hiding place (Broekhuizen and Maaskamp 1976;O'Donoghue and Bergman 1992;Rongstad and Tester 1971). In this study, almost all animals of the age class up to 4 days were found on bare soil or in fields with a low vegetation height (Voigt and Siebert 2019). Taken together, the change of place from the area of birth and the low coverage can lead to a rise in mortality rate due to an increased conspicuousness and visibility for predators.…”
Section: Survival Ratesmentioning
confidence: 52%
See 3 more Smart Citations
“…This can be explained by the fact that leverets of the genus Lepus leave their birth area between the second and fourth day of life to find their own daily hiding place (Broekhuizen and Maaskamp 1976;O'Donoghue and Bergman 1992;Rongstad and Tester 1971). In this study, almost all animals of the age class up to 4 days were found on bare soil or in fields with a low vegetation height (Voigt and Siebert 2019). Taken together, the change of place from the area of birth and the low coverage can lead to a rise in mortality rate due to an increased conspicuousness and visibility for predators.…”
Section: Survival Ratesmentioning
confidence: 52%
“…A recent study has shown that leverets performed a pronounced change in habitat between daytime and nighttime (Voigt and Siebert 2019), which is related to nursing behaviour. This fact was taken into account in the analysis.…”
Section: Data Processing and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This mortality is due to, among other factors, agricultural landing, diseases, and predation [11]. Juvenile mortality of the European hare may reach 90% [36]. Data on the Iberian hare suggest that nearly 60% of the young die, corresponding to an increase of 40% in the population numbers [14].…”
Section: The Top Threats To Hares In Europementioning
confidence: 99%